Increased Risk of Severe Sepsis in Hispanic Children Hospitalized With Acute Myeloid Leukemia. (November 2020) - Savage, Beth; Thomas-Hawkins, Charlotte; Cole, Peter D.; Stapleton, Jerod L.; de Cordova, Pamela B.
The purpose of this study, a secondary analysis of a publicly available database, was to identify racial and ethnic disparities in the risk of severe sepsis facing children undergoing the intensive therapy necessary to treat acute myeloid leukemia (AML). The sample consisted of 1, 913 hospitalizations of children, younger than 21 years, in the United States during the year 2016 with documentation of both AML and at least one infectious complication. Binary logistic regression models were used to examine the association between race/ethnicity and severe sepsis in children with AML and infection. We found that, after controlling for potential confounding variables, the odds of developing severe sepsis were significantly increased for Hispanic children compared with White children. There were no significant differences in the likelihood of the development of sepsis in Black, Asian, or other race children. The increased risk of severe sepsis for Hispanic children may contribute to the disparate rates of overall survival in this group. This inequitable rate of severe sepsis was evident despite the generally accepted practice of retaining children in the hospital throughout recovery of blood counts following AML therapy. Nurses are in a position to identify and eliminate modifiable risk factors contributing to this disparity.